Bilingualism and Script-Switching in a Poet’s Notebook from the Genizah - Ahmed, Mohamed Ali Hussein (Zutot, 2026)
This article investigates the linguistic and graphic form of the intertwining of the Arabic and Hebrew languages and their respective scripts in the pages of a medieval poetic notebook from among the manuscript fragments of the Cairo Genizah. The owner-producer of the notebook employed transcription, translation, code-switching and script-mixing, exploiting fully the bilingual nature of Jewish intellectual culture in the medieval Islamicate world. In this article we present the fragment and explain the probable strategy behind the language- and script-switching.